ANALYSIS ON THE SHIFT CONSTRUCTIONS IN INDONESIAN TRANSLATED TEXT - Julianti, Defi (Universitas Gunadarma, 2012)
The aim of this research is to describe the shifts occured in the translation of Englishpassive constructions into Indonesian. The data for the research are taken fromtwo novels, they are: the English version, entitled The Naked Face by SidneySheldon and its Indonesian version, entitled Wajah Sang Pembunuh by AntonAdiwiyoto. In this research, the writer uses a description method. It means all ofthe data that are analyzed are in the form of phenomenon description, not in theform of numbers but in the form of words and sentences. Data are classified intotwo categories, they are: 1) the occurence of shift of English passive – Indonesianpassive, and 2) the occurence of shift of English passive – Indonesian active. Thekinds of shifts that occur are structural and rank shift.